LEVEL REFLECTIVE ABSTRACTION MAHASISWA DALAM PEMECAHAN MASALAH MATEMATIKA - Walida, Sikky El; Fuady, Anies (Universitas Islam Malang, 2017)
Abstraction begins with a set of objects, then the object is grouped by important properties and relationships, then aborted nature and relationships that are not important. In this study the abstraction used is a reflection abstraction is a process that refers to the ability of students to reconstruct or re-reveal and reorganize the structures created from the activity and interpretation of students themselves to a new situation. This study aims to determine the level of student reflection abstraction process. The levels of reflection abstraction in this study are: (1) Interiorization, (2) Coordination, (3) Encapsulation, (4) Generalization. The mathematical problem solving in this study includes: (a) understanding the problem, (b) devising plan, (c) carrying out the plan, and (d) looking back (checking back). This research method is quite explorative with qualitative descriptive approach. This research reveals the level of student reflective abstraction in solving math problems. The problem presented is the task of mathematical settlement (TPM). The reflective abstraction is seen from the student behavior in solving the TPM. The process of reflective abstraction is studied using the Polya step. Polya settlement phase is (1) understanding the problem, (2) planning the problem, (3) problem solving, (4) checking again.